Glycolipids slow interfacial proton migration while preserving surface proton retention - Anna Maznichenko; Peter Pohl (Proceedings of the National Academy of Sciences, 2026)
Proton gradients power diverse biological processes, yet how interfacial proton migration is regulated remains unclear. Here we quantify how membrane composition controls interfacial proton migration using an approach that releases protons directly at the surface of a membrane patch via an embedded ionophore. Fluorometrically monitoring proton arrival at a distant patch across neutral, negatively charged, and positively charged membranes, we confirm that both the lateral surface diffusion coefficient and the activation barrier for proton release into the bulk vary rather modestly. In contrast to membrane electrostatics, membrane incorporation of glycolipids typical of thylakoid membranes—digalactosyldiacylglycerol and sulfoquinovosyldiacylglycerol—leads to a more pronounced reduction of the lateral proton diffusion coefficient, with comparatively small effects on the surface-to-bulk release barrier. Thus, interfacial proton migration is governed primarily by hydration-layer properties rather than membrane charge. These results establish membrane-anchored sugars as potent modulators of long-range proton conduction and provide a mechanistic framework for localized proton coupling in glycolipid-rich biological membranes.